2016
DOI: 10.1186/s12887-016-0565-2
|View full text |Cite
|
Sign up to set email alerts
|

Validating the Children’s Depression Inventory in the context of Rwanda

Abstract: BackgroundDepression is often co-morbid with chronic conditions, and when combined with HIV it can increase progression and reduce survival. A brief and accurate screening tool for depression among children living with HIV is necessary to increase access to mental health care and improve HIV-related outcomes in the long-term.MethodsA validation study was conducted, comparing the Children’s Depression Inventory (CDI) with a structured clinical assessment as the gold standard among children living with HIV ages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 28 publications
3
16
1
Order By: Relevance
“…A cross-sectional study of 562 HIV-infected adolescents from Malawi found a depression prevalence of 18.9% [29,30]. Within another study in Rwanda examining 100 HIV-infected children ages 7–14 years, the prevalence of depression reported was 25% [31]. A cross-sectional study of 82 HIV-infected adolescents ages 10–18-years old in Kampala, Uganda found that 51.2% had scores indicating significant psychological distress, 17.1% had attempted suicide in the past year, 19.5% had ever attempted suicide, and 30.5% had experienced psychotic symptoms in the past [32].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A cross-sectional study of 562 HIV-infected adolescents from Malawi found a depression prevalence of 18.9% [29,30]. Within another study in Rwanda examining 100 HIV-infected children ages 7–14 years, the prevalence of depression reported was 25% [31]. A cross-sectional study of 82 HIV-infected adolescents ages 10–18-years old in Kampala, Uganda found that 51.2% had scores indicating significant psychological distress, 17.1% had attempted suicide in the past year, 19.5% had ever attempted suicide, and 30.5% had experienced psychotic symptoms in the past [32].…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al ., Mutumba et al ., and Binagwaho et al .tested the validity of these existing mental health measurement instruments within Malawi, Uganda, and Rwande, respectively [29,31,46]. In Malawi, the validation findings suggested that the BDI-II had greater internal consistency and showed greater concordance with the CDRS-R results for this population [29].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations